CLINICAL AND ETIOLOGICAL SPECTRUM OF ACUTE FEBRILE ENCEPHALOPATHY IN ADULT PATIENTS: A PROPSPECTIVE STUDY FROM ODISHA, INDIA - Kar, Ayaskanta; Kumar Mishra, Pravin; Jena, Parsuram (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Acute febrile encephalopathy (AFE) is a medical emergency and might be an indicator of numerous systemic and central nervous system pathologies. In this backdrop, the present study was carried to evaluate the etiology and clinical features of encephalopathy succeeding short febrile illness in adults approaching to a tertiary care center. Methods: A prospective study was done up to 2 years in 110 patients beyond 14 years. The demographic variables were documented and along with routine examinations, cerebrospinal fluid analysis and radioimaging studies were performed. Results: The most common etiology of AFE was cerebral malaria (CM) that constitutes 39.1% (43 of 110) of total cases, followed by acute viral encephalitis (AVE), tuberculous meningitis (TBM), acute bacterial meningitis (ABM), sepsis associated encephalopathy (SAE), and enteric encephalopathy (EE) with 24 (21.8%), 20 (18.2%), 13 (11.8%), 5 (4.5%) and 2 (1.8%) cases, respectively. Death rate was 30.20% in CM, 23.07% in ABM, 20.83% in AVE, and 20% in TBM. Two cases of SAE and one case of EE also succumbed. Conclusion: CM found to be the furthermostcommunalsource of AFE followed by AVE, TBM, and ABM.